PERBEDAAN SIKAP SOSIAL SISWA ANTARA YANG BERTEMPAT TINGGAL DI KOMPLEK POLRI DAN DIPERKAMPUNGAN DI SMP NEGERI 2 MUARA BUNGO - Putri, Anne Mawidia (Jurnal Kopendik, 2022)
The environment where affects the formation of a student's attitude. The habits and culture of each of these places are different, thus allowing the different characteristics of the students who live in that place. This study aims to reveal the differences in the attitudes of students who come from the Police complex environment and in the villages of the students of SMP Negeri 2 Muaro Bungo by using a total sampling technique with a total sample of 80 students. Data collection techniques with a questionnaire. Data analysis was carried out with a quantitative approach, instrument testing, T-test with the help of SPSS 15. The results of the research from the t-test obtained that tcount was 5.839 while t-table at a significance level of 0.05 was 1.684, so tcount > ttable (5,839 > 1,684) then it can be concluded It can be concluded that there are differences in social attitudes between students who live in the Police complex and students who live in villages. The results of this study on guidance and counseling activities can be used as a reference to help students acquire a good attitude and do not differentiate between students from one another so as to support optimal learning outcomes.